Analysis of Women’s Poverty in Maluku Province - Daud, Jumerti; Pulubuhu, Dwia Aries T; Hasniati, Hasniati (ESTIMASI: Journal of Statistics and Its Application, 2024)
The Sustainable Development Goals (SDGs) aim to end poverty in all its forms everywhere and provide a gender-sensitive policy framework. Limited access to resources causes women to be more vulnerable to poverty and contributes to economic disadvantages, known as the feminization of poverty. Maluku Province is the fourth poorest province in Indonesia by 2022, with a poverty rate of 15.97 percent. The percentage of poor households headed by women is 7.03 percent, an increase of 0.83 percentage points from 2021. This research identifies the relationship between households headed by women and poverty in the Maluku Province. Secondary data were obtained from the National Socioeconomic Survey 2022 by the Central Bureau of Statistics. The sample size included 822 households headed by women. Binary logistic regression analysis was used in this study. The research found that area of residence, number of household members, education level, and employment sector significantly affected women's poverty status in Maluku. Furthermore, women's poverty was higher among rural residents. The findings highlight that the number of household members with family planning programs, better education, and government policies providing assistance for better agriculture can alleviate household poverty.